Field notes - Perry, Katrina Jane, 1983- (2019)
Language will betray vision. My ideas exist here in words that provoke meaning limited to the viewer’s experiential reference. Ultimately, one is left with only a feeling in relationship to a work of art. If the residual feeling is immanent, has the artwork succeeded? Further, how can success be measured in relationship to a subjective existence? A research-based practice allows me to come close to the tensions in life that obscure reality, dualities which divide and unite within the paradox of social-political systems and the human condition. My work allows the emotional distance necessary to process. The only objectivity – my responsibility as an artist and a human – is to be honest toward my subject and with myself. I traverse this land to gain ground. 33-days: August 5, 2016 to September 6, 2016. Alone, one bike, a circumnavigation of an island – of Iceland, 1200 plus kilometers of asphalt and gravel roads, 30 kilos of provisions, determination, rouge lipstick, and endurance. Begin.